The Asymmetric Risks of Automation in Latin America - Brambilla, María Irene (2022)
In this paper we characterize workers’ risks from automation in the near future in the six largest Latin American economies as a function of the exposure to routinization of the tasks that they perform and the potential automation of their occupation. We combine (i) indicators of potential automatability by occupation and (ii) worker’s information on occupation and other labor and demographic variables. We fi nd that the ongoing process of automation is likely to signifi cantly aff ect the structure of employment. In particular, unskilled and semi-skilled workers are more at risk of bearing a disproportionate share of the adjustment costs. Automation will probably be a more dangerous threat for equality than for overall employment.